2019
DOI: 10.1109/access.2019.2912183
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diamond Nanoparticle on the Friction Property of Sliding Friction Pair With Molecular Dynamics Simulation

Abstract: Effect of the diamond nanoparticle on the friction property of the sliding friction pair is investigated using the molecular dynamics simulation. A molecular dynamics simulation model without the diamond nanoparticle is also set up. The simulation is conducted at an external load of 60 nN. The results confirm that adding diamond nanoparticle can improve the friction property. With increasing the diameter, the angular velocity, and the indentation depth decrease inversely. Also, when the diameter varies from 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…99,100 Furthermore, it has been reported that Cu nanoparticles will signicantly damage the contact surface, especially under high loads. 101,102 Also, the friction coefficient of Cu nanoparticles becomes unstable with in the presence of carbon nanoparticles such as nano-diamond particles, decreasing sharply with an increase in the diameter of the nanoparticles. 100,101 Iron nanoparticles can partially avoid this problem and assist carbon nanoparticles to reduce damage on contact surfaces and increase the service life of mechanical components through non-bonded interactions of nanoparticles and the lubrication of nanoscrolls from the combination of Gr and nanoparticles.…”
Section: D Graphene-based Lubricating Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…99,100 Furthermore, it has been reported that Cu nanoparticles will signicantly damage the contact surface, especially under high loads. 101,102 Also, the friction coefficient of Cu nanoparticles becomes unstable with in the presence of carbon nanoparticles such as nano-diamond particles, decreasing sharply with an increase in the diameter of the nanoparticles. 100,101 Iron nanoparticles can partially avoid this problem and assist carbon nanoparticles to reduce damage on contact surfaces and increase the service life of mechanical components through non-bonded interactions of nanoparticles and the lubrication of nanoscrolls from the combination of Gr and nanoparticles.…”
Section: D Graphene-based Lubricating Materialsmentioning
confidence: 99%
“…101,102 Also, the friction coefficient of Cu nanoparticles becomes unstable with in the presence of carbon nanoparticles such as nano-diamond particles, decreasing sharply with an increase in the diameter of the nanoparticles. 100,101 Iron nanoparticles can partially avoid this problem and assist carbon nanoparticles to reduce damage on contact surfaces and increase the service life of mechanical components through non-bonded interactions of nanoparticles and the lubrication of nanoscrolls from the combination of Gr and nanoparticles. H. Washizu et al 103 developed a grapheneiron (GI) nanosheet-nanoparticle sandwich structure hybrid additive for lubrication in the frictional pair of iron contact, which indicates that iron particles can provide stability of the friction coefficient over a wide range of pressure and enable better protection for iron contact surfaces than other nanoparticle lubricants.…”
Section: D Graphene-based Lubricating Materialsmentioning
confidence: 99%
“…The step size was set to 0.1 fs, 0.2 fs, 0.3 fs, 0.4 fs, 0.5 fs, 0.6 fs, 0.7 fs, 0.8 fs, and 0.9 fs, 1 fs. For there were many uncertain factors in the pyrolysis reaction of transformer insulating paper, Monte Carlo algorithm (Force biased Monte Carlo, MC) was introduced to increase the randomness of the system to ensure that the model can be closer to the real cellulose pyrolysis condition [40], [41]. It was set to start MC once every 500-step molecular simulation.…”
Section: B Simulation Detailsmentioning
confidence: 99%
“…Coating graphene on surfaces of these contacts is found to result in a significant reduction of the friction coefficient. However, under a high load and after a certain time of test, graphene is highly damaged and loses its lubricity, leading to an increase in friction. , There are also many studies that reported the influence of nanoparticles on the friction sliding process. For the copper contact-tested friction, the friction coefficient has a steady value of 1.75 without the occurrence of the diamond nanoparticle and values lower than 0.6 with its occurrence, meaning that the friction coefficient decreases with increasing diameter of the nanoparticle . α-Iron shows a friction coefficient of ∼1 for the bare contact and values below 0.52 for the additional contacts where the carbon nanoparticles as carbon nanodiamonds or carbon nano-onions are added inside, depending on coverage of the nanoparticles on the surface and applied load, but almost being independent of the sliding velocity .…”
Section: Introductionmentioning
confidence: 99%